(NwELIKIJ g\TSBI(B. (NnO^X NEVNA(B:s (NrOMANY(B. (NrASSKAZYs - (NfICDVERALXD f(B. (Ns(B.s ((NfR\NSIS sKOTT(B)s; (NbATURIN s(B.s ((NmOSKWA(B:s (NhUDOVESTWENNAQ LITERATURA(B,s, 1985)
(Nw NASTOQ]IJ TOM (B"(NbIBLIOTEKI LITERATURY s{a(B" (NWHODQT LU^[IE PROIZWEDENIQ KLASSIKA AMERIKANSKOJ LITERATURY hh WEKA fR\NSISA sKOTTA fICDVERALXDA (B- (NROMANY (B"(NwELIKIJ g\TSBI(B" (NI (B"(NnO^X NEVNA(B", (NNAIBOLEE IZWESTNYE RASSKAZY(B.s
(NtIRAV(B: 100 000 (N\KZ(B.s
(NiNW(B.: 262373s